2023
DOI: 10.3390/jpm13111594
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Biological Therapy in Severe Asthma: Where We Are?

Lorenzo Carriera,
Marta Fantò,
Alessia Martini
et al.

Abstract: Biological drugs have revolutionized the management of severe asthma. However, a variable number of patients remain uncontrolled or only partially controlled even after the appropriate administration of a biologic agent. The combination of two biologics may target different inflammatory pathways, and it has been used in patients suffering from uncontrolled severe asthma with evidence of both allergic and eosinophilic phenotypes or severe asthma and type2 comorbidities. Combination therapy has also been used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…It is administered by subcutaneous injection at a dose of 210 mg every 4 weeks. According to the PATHWAY, NAVIGATOR, SOURCE, and DESTINATION trials, the clinical efficacy of tezepelumab has been demonstrated in patients with severe asthma with decreased exacerbation rate, increased prebronchodilator FEV1, improved quality of life, reduced OCS dose, and favorable long-term safety [ 76 , 77 , 78 , 79 ]. Additionally, as eosinophil counts and FeNO levels increased, so did their effectiveness in reducing asthma exacerbation.…”
Section: Biologic Therapies For Severe Asthmamentioning
confidence: 99%
“…It is administered by subcutaneous injection at a dose of 210 mg every 4 weeks. According to the PATHWAY, NAVIGATOR, SOURCE, and DESTINATION trials, the clinical efficacy of tezepelumab has been demonstrated in patients with severe asthma with decreased exacerbation rate, increased prebronchodilator FEV1, improved quality of life, reduced OCS dose, and favorable long-term safety [ 76 , 77 , 78 , 79 ]. Additionally, as eosinophil counts and FeNO levels increased, so did their effectiveness in reducing asthma exacerbation.…”
Section: Biologic Therapies For Severe Asthmamentioning
confidence: 99%